Bóg i niebo w poezji rewolucyjnej dwudziestolecia międzywojennego - Cieślak, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The author of the article discusses the great variety of the visions of the figure of God and the heaven in the revolutionary poetry between 1918 and 1939. God, the religion, the church or the synagogue were the symbols of the social oppression and the injustice or, on the contrary, the figure of God, especially Christ, was created as the most significant revolutionist and the symbol of the new, communist order. The article offers a presentation of many revolutionary, atheistic lyrics, which connect communist ideology with Jewish or Christian religious symbols. It is focused on the former futurists’ poetry (by Aleksander Wat, Bruno Jasieński, Anatol Stern) and the lyrics by the communist propagandists of the inter-war epoch.